2020
DOI: 10.1080/2372966x.2020.1716636
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents With Autism Spectrum Disorder and Social Skills Groups at School: A Randomized Trial Comparing Intervention Environment and Peer Composition

Abstract: This study used a randomized controlled trial to compare two distinct models of group social skills interventions with adolescents with autism spectrum disorder (ASD). Participants had a confirmed diagnosis of ASD, an IQ greater than or equal to 70, and were educated in the general education setting. Data from 62 adolescent participants who were randomized to one of two treatment conditions (SKILLS vs. ENGAGE) were analyzed. SKILLS participants had a diagnosis of ASD, or social difficulties. ENGAGE groups incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…Within the school setting, observation locations varied. Ten studies observed participants during unstructured social periods, including break time, recess, or lunch (Brock et al, 2018;Dean et al, 2020;Kasari et al, 2012Kasari et al, , 2016Kretzman et al, 2015;Locke, Rotheram-Fuller, et al, 2019;Locke, Shih, et al, 2019;Radley, 2017;Shih et al, 2019;Sreckovic et al, 2017). Seven studies observed the participants in the classroom during circle time, learning center time, or during group work (Carter et al, 2016;Dueñas et al, 2019;Hu et al, 2018;Jung et al, 2008;Kalyva & Avramidis, 2005;Kamps et al, 2002;Vivanti et al, 2019).…”
Section: Observation Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Within the school setting, observation locations varied. Ten studies observed participants during unstructured social periods, including break time, recess, or lunch (Brock et al, 2018;Dean et al, 2020;Kasari et al, 2012Kasari et al, , 2016Kretzman et al, 2015;Locke, Rotheram-Fuller, et al, 2019;Locke, Shih, et al, 2019;Radley, 2017;Shih et al, 2019;Sreckovic et al, 2017). Seven studies observed the participants in the classroom during circle time, learning center time, or during group work (Carter et al, 2016;Dueñas et al, 2019;Hu et al, 2018;Jung et al, 2008;Kalyva & Avramidis, 2005;Kamps et al, 2002;Vivanti et al, 2019).…”
Section: Observation Methodsmentioning
confidence: 99%
“…Five studies used observation protocols to measure social initiations and responses (Harper et al, 2007;Hu et al, 2018;Jung et al, 2008;Kalyva & Avramidis, 2005;Sreckovic et al, 2017), and two observation protocols measured interactions (Brock et al, 2018;Jung et al, 2008). Six studies used the Playground Observation of Peer Engagement (POPE; Kasari et al, 2012Kasari et al, , 2015Kretzman et al, 2015;Locke, Rotheram-Fuller, et al, 2019;Locke, Shih, et al, 2019;Shih et al, 2019), and an additional two studies used an adaptation of the POPE (Dean et al, 2020;Radley et al, 2017). The POPE was designed specifically to observe the social behaviors of participants with ASD and their TD peers during recess/break time and lunch.…”
Section: Observation Methodsmentioning
confidence: 99%
See 3 more Smart Citations